IDENTIFICATION OF BLOOD AND GASTROINTESTINAL PARASITES IN K-9 DOGS AT THE REPUBLIC OF INDONESIA STATE POLICE OF MALANG CITY RESORT - Adithya Fauzan; Nyoman Adi Suratma; Sri Kayati Widyastuti (Buletin Veteriner Udayana, 2024)
K9 dogs are one of the animals of the Indonesian National Police where they have a fairly extreme and heavy work environment in assisting tasks such as finding explosives, drug tracking operations, security operations and searching for victims of natural disasters such as landslides to earthquakes. This study was conducted to determine the incidence of infection and the types of blood and digestive tract parasites that infect K9 dogs in the Indonesian National Police Malang City Resort. The blood examination method used is by observing blood reviews with Diff-quick staining and fecal examination using the flotation concentration method which is then observed with a microscope. The results of the incidence of parasitic infections in K9 dogs of the Indonesian National Police Malang City Resort were 100%, namely from 10 dog samples, 50% were infected with blood parasites and 60% were infected with digestive tract parasites. In the blood test examination only found Babesia sp. while in the feces examination found Ancylostoma sp., Strongyloides sp. and Trichuris sp. It is recommended to take countermeasures in the form of routine anti-parasitic administration.